Cash Waqf Fundrising: The Glaring Gap in Marketing Communication Practice of BWI (Indonesian Waqf Board) - Anna Sardiana (Jurnal Ilmu Manajemen & Ekonomika, 2019)
The purpose of this paper is to analyze and discuss what is missing in cash waqf interest of Indonesian Muslim society. The study reveals several factors that affect less of cash waqf revenue including lack of information, less knowledge and media promotions factors. The paper outlines some of the communication pattern (promotion) that should be manifested in a waqf fund manager, particularly BWI such as being more proactive, approaching society through Islamic lecture, and do more advertisement. Finally, the paper highlights some of the communication issues that seem to be common between managing cash waqf and other business organizations such as marketing communication, promoting waqf fund manager GCGs, identifying potential waqif, or do more advertising. Descriptive, analytical, and qualitative analyses are used as methodology. The paper provides insights into management of cash waqf for Waqf boards or waqf fund managers and volunteers, enabling them to work more effectively to reach the target of cash waqf revenue by evaluating their communication pattern